1993
DOI: 10.1093/schbul/19.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Neuropathology of Schizophrenia

Abstract: This article reviews some 50 neuroanatomical postmortem studies published in the last 20 years. The majority of these studies demonstrated various types of subtle anomalies in limbic structures, that is, the hippocampus, parahippocampal gyrus, entorhinal cortex, amygdala, cingulate gyrus, and septum of schizophrenia patients. A number of schizophrenic symptoms might be related to structural and functional disturbances of these brain regions. But these studies also reported subtle changes in parts of the basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(115 citation statements)
references
References 161 publications
7
106
0
2
Order By: Relevance
“…A confluence of data from histopathological, neurochemical, in vivo imaging, and neuropsychological studies point to abnormalities of neuronal circuitry in corticolimbic regions particularly the prefrontal and cingulate cortices, and structures of the temporal lobe including the hippocampal formation. [88][89][90][91] Despite several compelling and interesting theories, the precise nature of these circuitry abnormalities is unknown, and further progress has been hampered by inconsistencies and poor replication of the findings. These problems are due in part to methodological issues and inadequate sample availability, but more importantly they bespeak the heterogeneity of the disease.…”
Section: Modeling Mechanisms: Defining the Questionsmentioning
confidence: 99%
“…A confluence of data from histopathological, neurochemical, in vivo imaging, and neuropsychological studies point to abnormalities of neuronal circuitry in corticolimbic regions particularly the prefrontal and cingulate cortices, and structures of the temporal lobe including the hippocampal formation. [88][89][90][91] Despite several compelling and interesting theories, the precise nature of these circuitry abnormalities is unknown, and further progress has been hampered by inconsistencies and poor replication of the findings. These problems are due in part to methodological issues and inadequate sample availability, but more importantly they bespeak the heterogeneity of the disease.…”
Section: Modeling Mechanisms: Defining the Questionsmentioning
confidence: 99%
“…The neurodevelopmental theory is based on several abnormal findings in patients with schizophrenia: abnormal architectural arrangements of individual nerve cells, cell clusters, or cortical layers (Bogerts, 1993), neurons that are misplaced, mis-sized, and disorganized (Harrison, 1997), absence of normal cerebral structural asymmetry (Crow et al, 1989), relative stability of cognitive dysfunction (Rund, 1998), absence of gliosis (Falkai et al, 1999), and premorbid behavioral abnormalities (Jones et al, 1994). All these observations are consistent with a disorder of prenatal brain development, and argue against the notion that schizophrenia is a progressive degenerative brain disorder (Bogerts, 1993;Mjellem and Kringlen, 2001;Weinberger, 1995;Harrison, 1995Harrison, , 1997. There is, consequently, a robust clinical rationale to support the validation of a neurodevelopmental model of schizophrenia (Lillrank et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these excitatory alterations could be used to delineate the neuronal circuits that, when functioning abnormally, produce psychotic behavior. Because of the important role of the EC in the processing of sensory input (Jones 1993) and disturbances in the neuronal organization and activity repeatedly observed in the EC neurons in schizophrenic brains (Falkai et al 1988;Arnold et al 1991;Bogerts 1993;Jakob and Beckmann 1994;Silbersweig et al 1995), caudal EC is a strong candidate for the brain area that is affected in schizophrenia. The relatively large number of affected neurons in the cEC and the wealth of information concerning the connectivity and physiology of the entorhinal-hippocampal system render this brain area a good candidate for a model system.…”
mentioning
confidence: 99%
“…Analysis of post-mortem material have suggested that brains of schizophrenic patients may display cytoarchitectonic disturbances in the entorhinal cortex (Falkai et al 1988;Arnold et al 1991;Bogerts 1993;Jakob and Beckmann 1994). CT scans of brains of schizophrenic patients have consistently demonstrated loss of gray matter in parahippocampal gyrus (Roberts 1990).…”
mentioning
confidence: 99%